Collaborative strategies: shared learning for the development of reading comprehension in primary school students (Praxis Educativa, 2021)
Collaborative work has a positive influence on student learning when it is used as a strategy to maximize the participation and involvement of students in the contents and activities to be developed. Therefore, the objective of this research was to identify shared learning as a collaborative strategy to improve reading comprehension of Primary Education students. Quantitative study of pre-experimental design with two groups, whose population and sample consisted of 46 students in the fourth grade of Primary Education. The results show that 66.7% of the students prior to the intervention presented low scores, however, after the application with the collaborative strategies, 58.3% went on to obtain a regular score and 25% reached a high score on the literal level of reading comprehension. In conclusion, shared learning as a collaborative strategy positively influences the reading comprehension of Primary Education students.